2021
DOI: 10.1007/s10450-020-00292-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule observation of diffusion and catalysis in nanoporous solids

Abstract: Nanoporous solids, including microporous, mesoporous and hierarchically structured porous materials, are of scientific and technological interest because of their high surface-to-volume ratio and ability to impose shape- and size-selectivity on molecules diffusing through them. Enormous efforts have been put in the mechanistic understanding of diffusion–reaction relationships of nanoporous solids, with the ultimate goal of developing materials with improved catalytic performance. Single-molecule localization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 129 publications
(274 reference statements)
1
46
0
Order By: Relevance
“…The intrinsic heterogeneity of nanocatalysts, however, complicates understanding the mechanisms of chemical processes in these systems using ensemble bulk measurements. More microscopic information can be obtained from single-molecule experimental approaches ( 8 14 ). These studies showed that there is a wide distribution in the rates of product formations and dissociations from the nanocatalysts.…”
mentioning
confidence: 99%
“…The intrinsic heterogeneity of nanocatalysts, however, complicates understanding the mechanisms of chemical processes in these systems using ensemble bulk measurements. More microscopic information can be obtained from single-molecule experimental approaches ( 8 14 ). These studies showed that there is a wide distribution in the rates of product formations and dissociations from the nanocatalysts.…”
mentioning
confidence: 99%
“…The ergodic theorem [110] implies that, under equilibrium conditions, the time and ensemble averages, i.e., averages taken over one and the same particle during subsequent time intervals or for many particles within the same time interval, yield identical mean values. This hypothesis has been experimentally proved for guest diffusion in nanoporous glass [111] by the combined application of SPT [90] and PFG NMR [88] As a consequence of the mutual interaction between the guest molecules, the difference in the physical situations as considered under the measurement of transport and selfdiffusion gives rise also to differences in the diffusivities. It is by this very reasoning that these differences should be expected to vanish in the limit of sufficiently small concentrations, i.e., under conditions where the interaction between the guest molecules becomes negligibly small -and distinction between equilibrium and non-equilibrium conditions becomes anyway meaningless [112].…”
Section: Equilibrium Vs Non-equilibriummentioning
confidence: 90%
“…Similar information can be provided by the application of microimaging [91,127] via IR microscopy [91,127,128]. More extensive information about the process of catalytic conversion is provided by SPT [90], enabling monitoring of even the individual reaction path ways [129][130][131].…”
Section: Laboratory Conditions Vs Conditions Of Technical Usementioning
confidence: 93%
See 2 more Smart Citations